CONTRASTIVE STUDY OF CLOSED INTERROGATIVE SENTENCE IN KOREAN AND INDONESIAN LANGUAGE - Pertiwi, Diyah Hayuning; Adnyana, Putu Pramania (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
This study discusses Korean and Indonesian morphosyntactic characteristics of closed interrogative sentences. The method used is descriptive qualitative with literature review and contrastive analysis. The results showed that there were differences and similarities in terms of closed interrogative markers, sentence structure, and sentence negation. The first difference in closed interrogative markers is that the marker in Korean is an interrogative sentence-ending (eomi) at the end of a sentence rather than a question word, whereas the marker in Indonesian is the question word apa at the beginning of the sentence and particle -kah at the beginning, middle or end of the sentence. Second, there are differences and similarities in sentence construction. Subjects that refer to the second person are omitted in Korean, whereas in Indonesian, the subject is required. The parallels lie in the fact that the predicate is a necessary component of sentence structure and that the presence of the object depends on the kind of verb used as the predicate. Thirdly, there is a distinction between Korean and Indonesian sentence negation in that Korean has a wider range of negation forms.